Whole genome sequence and comparative analysis of Borrelia burgdorferi MM1. - Neda Jabbari; Gustavo Glusman; Lena M Joesch-Cohen; Panga Jaipal Reddy; Robert L Moritz; Leroy Hood; Christopher G Lausted (PLoS ONE, 2018)
Lyme disease is caused by spirochaetes of the Borrelia burgdorferi sensu lato genospecies. Complete genome assemblies are available for fewer than ten strains of Borrelia burgdorferi sensu stricto, the primary cause of Lyme disease in North America. MM1 is a sensu stricto strain originally isolated in the midwestern United States. Aside from a small number of genes, the complete genome sequence of this strain has not been reported. Here we present the complete genome sequence of MM1 in relation to other sensu stricto strains and in terms of its Multi Locus Sequence Typing. Our results indicate that MM1 is a new sequence type which contains a conserved main chromosome and 15 plasmids. Our results include the first contiguous 28.5 kb assembly of lp28-8, a linear plasmid carrying the vls antigenic variation system, from a Borrelia burgdorferi sensu stricto strain.